IC 9376 A Chromatographic Method For Rapid Field Determination Of Parts-Per-Million To Percent Level Carbon Dioxide In Natural Gas - Philip W. Holland (The National Institute for Occupational Safety and Health (NIOSH), 1994)
This U.S. Bureau of Mines (USBM) report describes a chromatographic method that is used for rapid field determinations of carbon dioxide in natural gas streams at a USBM helium production facility. The method employs a commercially available portable gas chromatograph that is equipped with a 10-m fused-silica capillary column coated with a porous polymer. The instrument operating parameters permit determinations to be performed over a concentration range of 10 ppm to 10 pct with a frequency of 20 samples/h. The speed at which determinations can be performed is an important factor when evaluating efficiency or troubleshooting processes at the helium facility.